2021
DOI: 10.1186/s12905-021-01244-1
|View full text |Cite
|
Sign up to set email alerts
|

A large ovarian steroid cell tumor‐not otherwise specified with a unique combination of benign and malignant features as a challenging cause of oligomenorrhea and hirsutism in a 21‐year‐old Syrian female: a case report

Abstract: Background Ovarian steroid cell tumors represent a rare category of sex cord-stromal tumors that constitute less than 0.1% of all ovarian tumors. These neoplasms are classified into three main subtypes according to the cell of origin: Leidyg cell tumors, stromal luteomas, and steroid cell tumors not otherwise specified (SCTs-NOS). The latter subtype is defined as a neoplasm of an uncertain lineage that mostly affects middle-aged women, whereas it’s rare in younger ages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Androgenic symptoms such as hirsutism, virilization and disruption of normal menstrual cycles are seen in about half of the patients ( 11 ), Table I . Estrogenic manifestations in OSCT patients, including endometrial hyperplasia and postmenopausal metrorrhagia, were reported in <10 % of cases ( 5 , 12 ). Obesity and overweight, which are well known risk factors of IBC-NOS, were common features in OSCT ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Androgenic symptoms such as hirsutism, virilization and disruption of normal menstrual cycles are seen in about half of the patients ( 11 ), Table I . Estrogenic manifestations in OSCT patients, including endometrial hyperplasia and postmenopausal metrorrhagia, were reported in <10 % of cases ( 5 , 12 ). Obesity and overweight, which are well known risk factors of IBC-NOS, were common features in OSCT ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of crystals of Reinke is helpful to distinguish LCT from SCT-NOS, which are not accompanied by Leydig cell hyperplasia. The absence of spindle cells and bromatous background is useful to distinguish it from luteinized thecoma (12). General immunohistochemistry observations might be useful in problematic case, CD99 for example, is expressed in all sex cord stromal tumors except for SCT-NOS and broma, inhibin and calretinin are expressed less with bromas.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of crystals of Reinke is helpful to distinguish LCT from SCT‐NOS, the last is not accompanied by Leydig cell hyperplasia. The absence of spindle cells and fibromatous background is useful to distinguish SCT from luteinized thecoma 12 . General immunohistochemistry observations might be useful in problematic cases; for example, CD99 is expressed in all sex cord stromal tumors except for SCT‐NOS and fibromas.…”
Section: Discussionmentioning
confidence: 99%